The Effect of Tax Knowledge, Tax Sanctions, and Taxpayer Awareness On Individual Taxpayer Compliance - Made Puji Airlangga; I Ketut Jati (International Journal of Economics, Management and Accounting, 2025)
The implementation of the study to obtain and prove empirically related to the influence of tax knowledge, tax sanctions and taxpayer awareness on individual taxpayer compliance. The study with multiple linear regression with an approach, namely with a quantitative framework. The means of obtaining data is by distributing questionnaires. Based on the researcher's findings, empirical evidence shows that tax knowledge, tax sanctions, and taxpayer awareness have positive and significant effect on  individual taxpayer compliance at the East Denpasar Pratama Tax Service Office.